Exoskeleton Application to Military Manual Handling Tasks. (May 2022) - Proud, Jasmine K.; Lai, Daniel T. H.; Mudie, Kurt L.; Carstairs, Greg L.; Billing, Daniel C.; Garofolini, Alessandro; Begg, Rezaul K.
Objective: The aim of this review was to determine how exoskeletons could assist Australian Defence Force personnel with manual handling tasks. Background: Musculoskeletal injuries due to manual handling are physically damaging to personnel and financially costly to the Australian Defence Force. Exoskeletons may minimize injury risk by supporting, augmenting, and/or amplifying the user's physical abilities. Exoskeletons are therefore of interest in determining how they could support the unique needs of military manual handling personnel. Method: Industrial and military exoskeleton studies from 1990 to 2019 were identified in the literature. This included 67 unique exoskeletons, for which Information about their current state of development was tabulated. Results: Exoskeleton support of manual handling tasks is largely through squat/deadlift (lower limb) systems (64%), with the proposed use case for these being load carrying (42%) and 78% of exoskeletons being active. Human–exoskeleton analysis was the most prevalent form of evaluation (68%) with reported reductions in back muscle activation of 15%–54%. Conclusion: The high frequency of citations of exoskeletons targeting load carrying reflects the need for devices that can support manual handling workers. Exoskeleton evaluation procedures varied across studies making comparisons difficult. The unique considerations for military applications, such as heavy external loads and load asymmetry, suggest that a significant adaptation to current technology or customized military-specific devices would be required for the introduction of exoskeletons into a military setting. Application: Exoskeletons in the literature and their potential to be adapted for application to military manual handling tasks are presented.